Regulating Photocatalytic Selectivity of Anatase TiO2 with {101}, {001}, and {111} Facets. Issue 12 (18th August 2014) - Zhang, Jun; Chen, Sheng; Qian, Lisha; Tao, Xi; Yang, Lingxia; Wang, Hongbo; Li, Yangyang; Zhang, Erpan; Xi, Junhua; Ji, Zhenguo; Rohrer, G.
<x xml:space="preserve">Abstract</x> In this work, we demonstrate a novel approach to control the photocatalytic selectivity of TiO2 though different dominant crystal facets. {101}, {111}, and {001} facets exposed nanoscale anatase TiO2 were obtained by a simple hydrothermal route with different ratio of NH4+ and F−, then a calcined progress to clear surface adsorbent atoms. Results reveal that {101} exposed TiO2 has some remain binding N with a mode of unsaturated N3c exhibits selectively photocatalytic degradation of methylene orange (MO) in a methylene blue (MB) and methyl orange (MO) mixed solution, whereas TiO2 with exposed {111} and {001} facets exhibits photocatalytic selectivity for MB. The {111} facets of anatase TiO2 exhibit a better photocatalytic selective ability than {001} facets. It confirms that the photocatalytic selectivity can be affected by different dominant crystal facets. In a deeper analysis, there are many unsaturated O2c on the surface of {001} and {111} facets, which enhances adsorbent selectivity and relevant photocatalytic activity of MB, at the same time, the unsaturated O2c on the surface of {111} facets is much more than that on the surface of {001} facets results in a better photocatalytic selectivity of {111} facets. This research hopes that developing a new strategy for photocatalytic selectivity and providing a deeper understanding of different crystal facets of TiO2.